Trigramy, czyli powtarzalne trzywyrazowe struktury w dialogach zadaniowych - Szczyszek, Michał (Wydawnictwo „Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The present article analyses trigrams – words constructions that have properties of phrasemes. The studied trigrams have been excerpted from task-oriented dialogues (conducted between participants of a linguistic experiment). It turns out that phrasematic trigrams perform different communication and semantic functions: establishing and enhancing contact, feedback positive, “simple adverbiality” and “complex adverbiality”. The article is a follow-up to the author’s previous article on bi-grams: Bi-grams – Repetitive Two-word-structures in Task-oriented Dialogues.
Keywords: task-oriented dialogues; spoken Polish; communicative situations; communicative strategies.; trigrams; language communication; phrasemes